Governance and knowledge transformations in educational administration: Greek responses to global policies. (2nd January 2016) - Sifakakis, Polychronis; Tsatsaroni, Anna; Sarakinioti, Antigone; Kourou, Menie
Abstract : This article explores the localisation of the global and European discourse of educational governance in the Greek education system through the changes that have been introduced in the field of education administration since 2009 by the then socialist government. Our research aims to contribute to the critical policy literature on the spreading marketisation and privatisation in the governing of education around the world and in Europe – through the adoption of New Public Management and Educational Leadership models. In developing our theoretical perspective, we use the Foucauldian concepts of governmentality and discourse, and in order to conceptualise power and control relations in the organisation, transmission, acquisition, and evaluation of pedagogical knowledge, we draw on Bernstein's theory of symbolic control. Our study has examined how the field of education administration is governed through power and knowledge transformations. We trace these transformations by analysing systematically the pedagogic discourse through which the global governance discourse is relayed and becomes a 'regime of truth' within public policy and practice in Greece. We argue that such changes have significant implications for everyday educational practice and for the kinds of knowledge that are considered legitimate, and they may affect educational professionals' subjectivities in fundamental ways.